Learning by doing: Smartphone app in undergraduate medical students' research - C Sahanaa; Amit Kumar Mishra (Journal of Education and Health Promotion, 2018)
INTRODUCTION: In communication process, feedback plays a major role. Usually, a formal/informal feedback is collected from students on their experience and understanding about the tasks given by the mentor to assess the learning process. Receiving high-quality feedback (positive or negative) is valuable from multiple perspectives. Students may or may not enjoy sessions on innovative teaching–learning methods; in that case, feedback helps to modify it into a more effective and acceptable method of teaching. METHODOLOGY: With an objective to understand the students' perception on a smartphone app in community-based research, a cross-sectional study was planned among undergraduate students posted for the re-orientation of medical education. Epicollect5, a mobile app, was used for data capture. Students were requested to submit their feedback by using the same app which they had used during the survey. The received feedback was analyzed and presented in proportions. RESULTS: Students shared that the new tool was easy to install (97.5%), user friendly (100%), saved time in data collection and data entry (100%), and they also missed the usual practice of paper-based questionnaire survey (12.5%) and data entry in excel sheet (7.5%). CONCLUSION: The students liked and enjoyed the paperless method of data collection and entry which saved time and improved the quality of the data. They were also interested to learn more on the designing or framing the questionnaire in app and planned to use the app in future research. The feedback conveyed the immense welcome for new technology by the students into medical curriculum.